First Upper Triassic Diptera (Insecta) from Germany - Lukashevich, Elena Dmitrievna; Ansorge, Jörg (Zootaxa, 2024)
First Upper Triassic dipterans (Nematocera) are described based on isolated wings from Fuchsberg near Seinstedt (Sevatian, uppermost Norian of Lower Saxony, Germany): Crivoptychoptera nebrias gen. et sp. nov. (Psychodomorpha, Ptychopteridae), Ptychopteridae incertae sedis, Dohloboyia triassica gen. et sp. nov. (Bibionomorpha, Boholdoyidae) and Chironomidae incertae sedis (Culicomorpha). All taxa under discussion present the oldest occurrences of their families. Geological background and composition of the Upper Triassic insect fauna of Seinstedt are briefly discussed.